Diagnostic performance of the Bengali version of inflammatory back pain criteria in patients with axial spondylarthritis: a case control study - Sultan, Mohammad Imtiaz; Chowdhery, Mohammad Kafil Uddin; Islam, M. Toufiqul; Bhattacharjee, Ananya (International Journal of Research in Medical Sciences, 2026)
Background: Axial Spondyloarthritis (axSpA) is a chronic inflammatory disease affecting the spine, which requires accurate and early diagnosis for effective management. Inflammatory back pain (IBP) is a key symptom of axSpA. While several diagnostic criteria sets for IBP exist, limited data is available on the Bengali version of these criteria. This study aimed to evaluate the diagnostic performance of the Bengali version of IBP criteria sets (Calin, Berlin set 8a, Berlin set 7b and ASAS) in patients with axSpA and mechanical back pain (MBP). Methods: A total of 100 participants (50 axSpA patients and 50 MBP controls) were enrolled between April 2019 and September 2019 at Chattogram Medical College Hospital. Sensitivity, specificity, positive and negative predictive values and likelihood ratios were calculated for each IBP criteria set. ROC curve analysis was performed to assess overall diagnostic accuracy. Results: The sensitivity of the Bengali Calin criteria was 88.4%, with a specificity of 78.9%. Berlin set 8a criteria demonstrated the highest sensitivity (92.3%) but lower specificity (77.0%). ASAS IBP criteria performed moderately with 78.0% sensitivity and 69.5% specificity. Conclusions: The Bengali version of IBP criteria sets demonstrated strong diagnostic performance, with Berlin set 8a showing the highest sensitivity. These tools can aid in the early detection of axSpA in clinical settings in Bangladesh. Future research should focus on validating these criteria in larger, diverse populations.